2011
DOI: 10.1007/s11033-011-1381-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between ATM polymorphisms and cancer risk: a meta-analysis

Abstract: To date, epidemiological studies have assessed the association between Ataxia-telangiectasia mutated (ATM) gene polymorphisms and cancer risk, including lung cancer, breast cancer, glioma and pancreatic cancer. However, the results of these studies remain controversial. We aimed to examine the associations between two SNPs (rs664143 and rs664677) and cancer risk by conducting a meta-analysis of case-control studies. A total of 12 publications were included in this meta-analysis, 8 for rs664143 and 7 for rs6646… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…In addition, distinguishing between deleterious and neutral ATM alterations is required to allow the definition of standard-of-care clinical guidelines for the management of ATM carriers and their families [11]. Systematic review and meta-analysis of ATM sequencing data have been conducted to evaluate the health risks for parents and siblings of A-T patients, but similar large-scale screenings for ATM carriers in the general population by direct sequencing are not cost-effective yet [13]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, distinguishing between deleterious and neutral ATM alterations is required to allow the definition of standard-of-care clinical guidelines for the management of ATM carriers and their families [11]. Systematic review and meta-analysis of ATM sequencing data have been conducted to evaluate the health risks for parents and siblings of A-T patients, but similar large-scale screenings for ATM carriers in the general population by direct sequencing are not cost-effective yet [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Other studies have identified functional variants associated with increased lung cancer or thyroid cancer risk (30,31). Finally, inherited ATM mutations are also felt to play a role in familial pancreatic ductal adenocarcinoma (32)(33)(34).…”
Section: Germ-line Atm Heterozygosity and Cancer Susceptibilitymentioning
confidence: 99%
“…Single-nucleotide polymorphisms (SNPs) of ATM have been associated with cancer susceptibility (Shen et al, 2012). Among them, ATM-111 (G>A), a common functional SNP in the promoter region of the ATM gene, was reported to be a binding site of transcription factors that affect the ATM expression Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%